Statistical Methods for History Matching of Hydrological Model - Tjia, Dewi (Curtin University, 2016)
Four history matching methods were used to calibrate the parameters of the LUCICAT model for three catchments in Western Australia. The methods used were ant colony optimization (ACOR and DACOR), Robust Parameter Estimation and Gauss Levenberg Marquadt. These methods were applied directly and indirectly, and in the latter case multidimensional Kriging and artificial neural networks were used to build proxy models for LUCICAT. All HM methods performed favourably well.